Analisis Dampak Penyetopan Ekspor Emas terhadap Devisa dan Harga Emas dalam Negeri Di Masa Mendatang - Rahmayati, Suci; Firmansyah, Ricky; Pamungkas, Rizal Akda; a, Silvia (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 3 (2023): Vol.12.3. MARET 2023[166-230], 2023)
The purpose of this study was to determine the impact of the stoppage of gold exports that had been planned by the government, both on the country's foreign exchange and on the price of gold in the country. The method used in this research is a literature study. Literature study in this research is a series of activities carried out using library data collection methods, reading and recording, and managing data obtained from various sources in an objective, systematic, analytical and critical manner which will address the results of this study namely; 1) to find out whether the gold export ban policy can affect the country's foreign exchange. 2) whether it will generate greater foreign exchange earnings due to added value. 3) and whether there will be an increase in domestic commodity prices, especially gold. Previously, Indonesia was in 7th place from 2018 to 2020 with gold production of 130 tons to 139 tons. Even so, the gold that Indonesia exports is only raw gold which will be turned into gold which is a finished material in other countries, and besides that, Indonesia also only has gold reserves of only 78.6 tons. Thus, Indonesia will not stop gold but will carry out downstream operations where exports continue but only the type of gold is different and can affect the country's foreign exchange. Keywords: Foreign Exchange, Export, Gold, Downstream, Commodity